하노이 북미 정상회담 이후 북중·한중 관계 변화와 한반도 평화체제 구축 - 이재영; Jaeyoung Lee (한국과 국제정치, 2020)
2019년 2월 하노이 북미 정상회담 이후 한중관계는 여러 차례의 정상회담과 고위급 회담에도 불구하고, 미국 요인과 사드 문제라는 큰 걸림돌 때문에 여전히 전략적 협력이 심화되지 못하고 있다. 반면 북·중 관계는 다섯 차례의 정상회담과 시진핑 주석의 방북으로 전통적 우의 관계는 회복되었음에도 북한 경제의 대중 의존도는 오히려 증가했다. 우리는 중국과의 외교·안보 협력 강화를 통해 중국의 적극적인 역할과 협조를 구할 뿐만 아니라 이러한 북·중 관계 복원을 활용함으로써 북한을 북미협상 테이블로 다시 불러들여야 할 것이다. 결론적으로 한반도평화체제 구축을 위해 우리는 한미동맹과 한중동반자 관계 사이 상호보완성을 강화함으로써 동맹과 동반자 관계의 ‘건설적 병립’을 추진해야 할 것이다. After the summit between North Korea and the United States in Hanoi in February 2019, despite several summits and high-level talks between South Korea and China, strategic cooperation has not been deepened due to major obstacles such as US factors and THAAD issues. On the other hand, after five summit meetings and President Xi Jinping's visit to North Korea, the traditional friendship between North Korea and China has been recovered. However, North Korea's economic dependence on China has risen. South Korea should not only seek China's active role and cooperation by strengthening diplomatic and security cooperation with China, but also bring North Korea back to U.S.- North Korea denuclearization negotiation table by utilizing this restoration of North Korea-China relations. In conclusion, in order to establish a peace regime on the Korean Peninsula, we must promote a “constructive parallel” between the alliance and partnership by strengthening the complementarity between the ROK-US alliance and the ROK-China partnership.